What have we learned from a case of convalescent plasma treatment in a two-time kidney transplant recipient COVID-19 patient? A case report from the perspective of viral load evolution and immune response - Aldunate, Fabian; Fajardo, Alvaro; Ibañez, Natalia; Rammauro, Florencia; Daghero, Hellen; Arce, Rodrigo; Ferla, Diego; Pereira-Gomez, Marianoel; Salazar, Cecilia; Iraola, Gregorio; Pritsch, Otto; Hurtado, Javier; et al. (Frontiers in Nephrology, 2023)
COVID-19, an infectious disease caused by SARS-CoV-2 virus, can provoke a vast range of clinical manifestations, ranging from asymptomatic to potentially life-threatening complications. At the beginning, convalescent plasma therapy has been proposed as an effective alternative to treat severe cases. The aim of this study was to follow over time a two-time renal transplanted COVID-19 severe patient treated with convalescent plasma from an immunological and virologic perspective. A 42-year-old female patient, two-time kidney transplanted was hospitalized with COVID-19. Due to worsening of respiratory symptoms, she was admitted to the intensive care unit where she received two doses of convalescent plasma. We analyzed the dynamics of viral load in nasopharyngeal swab, saliva and tracheal aspirate samples, before and after convalescent plasma transfusion. Pro-inflammatory cytokines and antibody titers were also measured in serum samples. A post-treatment decrease in viral load was observed to be sharp in saliva and nasopharyngeal swab samples, and slight in tracheal aspirate samples. Furthermore, we evidenced an increase of antibody titers post transfusion, accompanied with a decrease of several cytokines responsible of the cytokine storm.